PENGARUH KEBIASAAN BELAJAR TERHADAP PRESTASI BELAJAR SISWA KELAS VIII-B di MTsN 1 PAMEKASAN - Nurul Maulidina; Ainun Nikmah (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2025)
Each student has an unequal capacity in absorbing learning, there are students who are less than optimal in learning and there are also some students who have achievements compared to other students. From the results of research that has been carried out by researchers in class VIII-B of MTsN 1 Pamekasan, it turns out that one of the things that has an impact on achievement is student learning habits, especially students who excel. This study aims to find out the study habits of outstanding students in class VIII-B are in students who are ranked in the top 5 and is the effect of student learning habits on student achievement. The technique used in collecting data is using observation and questionnaire sheets. From the results of the study it was found that students' study habits have a very large influence on student achievement, especially in the academic field. Among the learning habits of outstanding students are making study schedules, diligently repeating or reviewing material, taking notes from the teacher's explanations, and asking for material that has not been understood. This is a learning habit, namely the way or effort made by students in order to achieve learning goals and pursue learning achievement.